Pengaruh Sanitasi Makanan dan Kontaminasi Bakteri Escherichia coli Terhadap Penyakit Diare - Dion Pardameian Hutasoit (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Diarrhea is the consistency of feces that is softening to liquid with the frequency of production of feces three times or more in a day. One of the risk factors of diarrhea is the food sanitation is not good and the contamination of Escherichia coli microorganisms. Objectives: Learn more about the influence of food sanitation and Escherichia coli contamination to diarrhea disease. Methods: Using literary studies from both national and international journals by summarizing the topic of the discussion and comparing the results presented in the article. Results: Food sanitation is closely related to hygiene, where a person with good hygiene must be supported by adequate sanitation. In human bacteria, E. coli that often causes diarrhea is grouped into four, namely Enterotoxigenic E. coli (ETEC), enteroinvasive E. coli (ETEC), Enteropathogenic E. coli (EPEC), and Enterohemorrhagic E. coli (EHEC). Conclusion: food sanitation and contamination of E. coli are very influential in the incidence of diarrhea disease